Ceramics in transition - Holmqvist, Elisabeth. (Oxford)
viii, 193 sayfa
Keywords: “This book focuses on the utilitarian ceramic traditions during the socio-political transition from the late Byzantine into the early Islamic Umayyad and ‘Abbasid periods, in southern Transjordan and the Negev. Production clusters, manufacturing techniques, distribution patterns, and material links between communities are analysed“ --